Burials, corpses and offerings in the Bronze Age of NW Iberia as agents of social identity and memory - Bettencourt, Ana M. S. (2010)
In this text we analyse several materialities related to the world of death during the Bronze Age in the Northwest of the Iberian Peninsula with the purpose of discussing the long-term role of the corpses, the sepulchral places and the offerings as agents of legitimization of the territory, of memory and of creation and maintenance of the group identity. The first framed hypothesis is that there seems to be different conceptions of death between the highlands, associated with communities with a more pastoral way of life, and the lowlands, more in connection with agricultural societies. The second one establishes that in both types of communities it was always in the Early Bronze when corpses had a greater weight as agents of legitimization of territory and identity. Finally, the third and last hypothesis assumes that from the Middle Bronze Age on the scenarios of power negotiation and maintenance are gradually transferred and spread into other contexts, such as the sites with rock engravings, the places of metal deposits and the settlements themselves. This may be in accordance with the possible increase of the practice of cremation in which the “consumed body” loses “visibility”.